2021
DOI: 10.3390/agronomy11030410
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiome Composition and Diversity under the Long-Term Application of Spent Mushroom Substrate and Chicken Manure

Abstract: Waste exogenous organic matter, including spent mushroom substrate (SMS) and chicken manure (CM), can be used as the basis of a soil-improving cropping system in sustainable agriculture. However, there is—as yet—a lack of information about important quality indicators such as the fungal community relative abundance, structure and biodiversity in soils treated with these additives. In this study, the responses of the soil fungal community composition and mycobiome diversity to SMS and CM application compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 71 publications
(106 reference statements)
6
26
0
Order By: Relevance
“…Hence, the addition of gypsum changes the soil properties and consequently leads to a positive effect on soil microbiota. Furthermore, mushroom residue and oyster shell powder also had a positive impact on soil microbial communities, consistent with previous findings [ 21 ] that mushroom residue improved the fungal communities. The possible explanation for increasing fungal community under mushroom residue may be related to an improvement of the soil environment, e.g., soil pH [ 69 ], thus leading to soil microorganisms having a healthier ecosystem [ 21 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Hence, the addition of gypsum changes the soil properties and consequently leads to a positive effect on soil microbiota. Furthermore, mushroom residue and oyster shell powder also had a positive impact on soil microbial communities, consistent with previous findings [ 21 ] that mushroom residue improved the fungal communities. The possible explanation for increasing fungal community under mushroom residue may be related to an improvement of the soil environment, e.g., soil pH [ 69 ], thus leading to soil microorganisms having a healthier ecosystem [ 21 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, mushroom residue and oyster shell powder also had a positive impact on soil microbial communities, consistent with previous findings [ 21 ] that mushroom residue improved the fungal communities. The possible explanation for increasing fungal community under mushroom residue may be related to an improvement of the soil environment, e.g., soil pH [ 69 ], thus leading to soil microorganisms having a healthier ecosystem [ 21 , 70 ]. Similarly, we found that oyster shell powder also had a significant effect on improving the soil microbial diversity and community composition, and these results are consistent with previous findings [ 18 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Ascomycota is the most common and diversified phylum of eukaryotes, as well as the decomposition of organic substrate [ 22 ], and we discovered it to be the most common fungal phylum in the red soil. Basidiomycota includes some of the most well-known fungi for their ability to generate huge fruiting bodies, as well as plant parasite fungi that cause wood degradation and litter decomposition [ 51 , 52 ]. Because of their symbiotic relationship with the host plant’s roots, this fungus category could be very advantageous to plants, as they store mineral nutrients, metabolites, and water [ 52 ].…”
Section: Discussionmentioning
confidence: 99%